2011
DOI: 10.3109/10641963.2011.577487
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Switching from a Combination of Angiotensin II Receptor Blockers other than Losartan and Thiazides to a Fixed Dose of Losartan/Hydrochlorothiazide on Uric Acid Metabolism in Hypertensive Patients

Abstract: Among the angiotensin II receptor blockers (ARBs), losartan (LOS) has uricosuric action. The clinical benefits of LOS compared with those of other ARBs may be apparent when it is combined with diuretics, which have an unfavorable influence on serum uric acid (SUA). The effects of switching from combinations of ARBs other than LOS and thiazides to a fixed-dose combination comprising 50 mg LOS and 12.5 mg hydrochlorothiazide on blood pressure (BP), SUA, percent fractional excretion of UA (FEUA), and urine pH wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other antihypertensive drugs including amlodipine and diuretics did not significantly increase the risk of HUA. Previous literature showed that losartan, an ARB, could promote UA excretion, thereby reducing UA levels (9,10). Except for losartan, other ARBs did not show definite UA-lowering effects (26).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other antihypertensive drugs including amlodipine and diuretics did not significantly increase the risk of HUA. Previous literature showed that losartan, an ARB, could promote UA excretion, thereby reducing UA levels (9,10). Except for losartan, other ARBs did not show definite UA-lowering effects (26).…”
Section: Discussionmentioning
confidence: 90%
“…Big data on the prevalence of HUA in Chinese hypertensive patients are lacking. In addition, previous studies revealed that thiazide diuretics increased the serum UA level (8), while angiotensin II receptor blocker (ARB) losartan decreased the UA level to some degree (9,10), which indicated the contrasting effects of different antihypertensive agents on UA. However, these effects must be evaluated in a larger hypertensive population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that losartan, not other ARBs, has a beneficial effect to reduce serum uric acid levels in several studies [24][25][26]. It seemed obvious that losartan was effective to reduce serum uric acid levels in the patients with higher serum uric acid levels.…”
Section: Discussionmentioning
confidence: 96%